A Study of Planning Problems in an Islamic Perspective: The Method of Maudhui Interpretation and the Results of Strategic Principles - Yuli Supodo; Muhammad Hariyadi (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2026)
Modern planning in Islamic education management often struggles to balance ikhtiar (rational effort) and divine tawakkal (reliance on Allah), leading to failures in risk mitigation in the Society 5.0 era. This article aims to address this issue by revealing holistic strategic principles from Qur'anic maudhui tafsir. The qualitative library research method applies thematic analysis on QS. Al-Anfal:30 (qadar), QS. Al-Hasyr:18 (ikhtiar), and QS. Ali Imran:159 (tawakkal), using classical tafsir by Ibnu Katsir (1999) and contemporary by Quraish Shihab (2007) and Hamka (2003), triangulated with Islamic management literature. Results reveal a three-pillar model: qadar as a long-term vision baseline, incremental ikhtiar for budgeting, and post-shura tawakkal mitigation, enhancing budget management efficiency by 25-35% compared to secular approaches, as shown in a contemporary Islamic management simulation. Impacts include holistic RPS recommendations integrating spiritual, rational, and participatory dimensions for Islamic universities, with prospects for empirical testing. The conclusion affirms Maudhui Tafsir as an original solution for planning that balances qadar, ikhtiar, and tawakkul.